The hidden meaning in Hamasaki Ayumi's Secret song lyrics based on Riffaterre’s semiotics analysis - Dewanti, Yustika Fatimatuzzahro (Universitas Dian Nuswantoro, 2021)
There is always a hidden meaning in literary works, concise works like poetry. It is always there even though it is not visible in the expression of its words. This is one of the main factors that characterize poetry, a string of impressive, dense, and implied meaning. This study attempts to describe the meaning contained in the lyrics of the song Secret by Hamasaki Ayumi by using the semiotic theory of Riffaterre's poetry. In this study, song lyrics are treated like poetry because of the similarity in form and nature. The results of data analysis found that the main message to be conveyed by the author is freedom. The author feels confined and bound by his status as a famous artist. He feels that he does not have his world because his world belongs to the public.